2013
DOI: 10.1038/nmeth.2510
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic progenitor cell lines with myeloid and lymphoid potential

Abstract: Investigation of immune cell differentiation and function is limited by shortcomings of suitable and scalable experimental systems. Here we show that an estrogen–regulated form of HOXB8 that is retrovirally delivered into mouse bone marrow cells can be used along with FLT3 ligand to conditionally immortalize early hematopoietic progenitor cells (Hoxb8–FL). Hoxb8–FL cells have lost self–renewal capacity and megakaryocyte/ erythroid lineage potential, but sustain myeloid and lymphoid potential. Hoxb8–FL cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
180
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(192 citation statements)
references
References 40 publications
5
180
0
1
Order By: Relevance
“…To further explore the role of LAR phosphatases in murine pDCs, we utilized a conditionally transformed progenitor cell line HoxB8-FL that can be differentiated into functional pDCs (Redecke et al, 2013). We derived HoxB8-FL cells expressing yellow fluorescent protein (YFP) reporter from the IFN-β-encoding Ifnb gene and differentiating into pDCs with >90% efficiency (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the role of LAR phosphatases in murine pDCs, we utilized a conditionally transformed progenitor cell line HoxB8-FL that can be differentiated into functional pDCs (Redecke et al, 2013). We derived HoxB8-FL cells expressing yellow fluorescent protein (YFP) reporter from the IFN-β-encoding Ifnb gene and differentiating into pDCs with >90% efficiency (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…5B). The HoxB8-FL cell line was recently reported to have both myeloid and lymphoid potential (29). We therefore also generated expression profiles for 107 HoxB8-FL single cells, which, when projected onto the diffusion plot, confirmed that the HoxB8-FL expression state resembles that of primary bone marrow cells from the LMPP trajectory.…”
Section: Resultsmentioning
confidence: 63%
“…In addition to GATA1 and CEPBA, recovered for erythroid lineage and myeloid lineages, respectively (Fig. 2c), along the erythroid cell differentiation trajectory, we uncovered several additional potential regulators for HSCs (ATF3 34 , HOXB8 35 ) and MEPs (LMO2 36 ,TAL1 30 ) (Supplementary Fig.15 ).…”
Section: Supplementary Figure 15 Stream Automatically Discovers Impormentioning
confidence: 95%